An autonomous, non-cooperative, wide-area Traffic Monitoring System using space-based Radar (TRAMRAD) - Hounam, D.; Baumgartner, S. V.; Bethke, Karl-Heinz; Gabele, Martina; Kemptner, Erich; Klement, Dieter; Krieger, Gerhard; Waegel, K. (International Geoscience and Remote Sensing Symposium (IGARSS), Seoul, 25-29.07.2005, 2005)
To meet the challenges of ever increasing road traffic and the associated economic and sociological impacts, new techniques and technologies for better traffic management are needed. The TRAMRAD project (Traffic Monitoring with space-based Radar) aims to profit from research and development in earth observation and advances in radar remote sensing techniques to define a future space-based sensor system for the wide-area monitoring of road traffic. The paper describes the requirements for the system and the concepts being investigated. In particular, it discusses the complex detection conditions, the requirements on the radar instrument and the methods for processing the data. Possible system concepts are described and their capabilities are discussed. © 2005 IEEE.
DLR Import::2019-04-03